Developing a framework of core competencies in implementation research for low/middle-income countries. Issue 5 (3rd September 2019) - Alonge, Olakunle; Rao, Aditi; Kalbarczyk, Anna; Maher, Dermot; Gonzalez Marulanda, Edwin Rolando; Sarker, Malabika; Ibisomi, Latifat; Dako-Gyeke, Phyllis; Mahendradhata, Yodi; Launois, Pascal; Vahedi, Mahnaz
Abstract : The field of implementation research (IR) is growing. However, there are no recognised IR core competencies in low/middle-income countries (LMICs), nor consistent curriculum across IR training programs globally. The goal of this effort is to develop a framework of IR core competencies for training programs in LMICs. The framework was developed using a mixed-methods approach consisting of two online surveys with IR training coordinators (n = 16) and academics (n = 89) affiliated with seven LMIC institutions, and a modified-Delphi process to evaluate the domains, competencies and proficiency levels included in the framework. The final framework comprised of 11 domains, 59 competencies and 52 sub-competencies, and emphasised competencies for modifying contexts, strengthening health systems, addressing ethical concerns, engaging stakeholders and communication especially for LMIC settings, in addition to competencies on IR theories, methods and designs. The framework highlights the interconnectedness of domains and competencies for IR and practice, and training in IR following the outlined competencies is not a linear process but circular and iterative, and starting points for training may vary widely by the project, institution and challenge being addressed. The framework established the need for a theory-based approach to identifying proficiency levels for IR competencies (ie, to determine proficiency levels for IR based on generalisable educational theories for competency-based education), and the relevance of various IR competencies for LMICs compared with high-income settings. This framework is useful for identifying and evaluating competencies and trainings, and providing direction and support for professional development in IR.